Development of bacterial cellulose nanofibers/konjac glucomannan-based intelligent films loaded with curcumin for the fresh-keeping and freshness monitoring of fresh beef. (December 2022) - Li, Nan; Yang, Xingbin; Lin, Dehui
Abstract: In this study, konjac glucomannan (KGM)-based intelligent films with different curcumin contents (0%, 1%, 3%, 5% and 7%) and 2% bacterial cellulose nanofibers (BCNs) were prepared, and their microstructure, physical properties, fresh-keeping performance and monitoring properties were studied. Microstructure showed that curcumin significantly affected the morphology and structure of the film matrix. FTIR analysis showed that hydrogen bonds were formed between the interactions of curcumin and film matrix. XRD and TGA analysis showed that the crystallinity and thermal stability of the films increased significantly with the increase of curcumin. Moreover, the mechanical properties and barrier properties of KGM-based intelligent films were improved with the increase of curcumin contents, as well as the antioxidant and antibacterial properties. Especially, KGM-based intelligent film loaded with 3% curcumin showed the best properties. Additionally, KGM-based intelligent films loaded with 3% curcumin were used for the packaging of the fresh beef. The results showed that the freshness of the beef packaged with 3% curcumin-loaded film was the best and the color of the film gradually turned red as the packaged beef was deteriorated, indicating that the film can not only used for the preservation of beef, but also can be used as a pH colorimetric indicator of meat. Highlights: Curcumin was used as an indicator in KGM-based intelligent films. Curcumin improved antioxidant and antibacterial properties of KGM-based intelligent films. KGM-based intelligent films were able to monitor the freshness of fresh meat in real time. KGM-based intelligent films displayed great potential application in food packaging field.